Reading Augustine in the Reformation: The Flexibility of Intellectual Authority in Europe, 1500–1620. By Arnoud S. Q. Visser - Methuen, Charlotte (The journal of theological studies, 2012)
Arnoud Visser’s fascinating book reflects some of the fruits of his involvement in the After Augustine project at the University of St Andrews. Visser offers a nuanced and critical discussion of the ways in which Augustine was edited, presented, and read by a variety of parties during the Reformation. It has often been said that Augustine’s theology was a weapon employed on both sides of every Reformation debate, and Visser not only demonstrates that this was indeed so, but illustrates the range of techniques of reading and presenting Augustine which made this possible.